Detoxification of Aflatoxin B1 by Extracellular Enzymes of Aspergillus oryzae KKB4 - Sardjono Sardjono; Endang S Rahayu; Sri Raharjo; Kapti Rahayu (Indonesian Food and Nutrition Progress, 2004)
Aflatoxin B1 (AFB1) is the common mycotoxin in food from tropical countries and the most harmful mycotoxin to human health. Detoxification is important step in food processing, in order to get foods free from AFB1, because of the resistance of this mycotoxin againts the ordinary processing conditions. The ability of Aspergillus oryzae KKB4 on detoxification of AFB1 was evaluated. The strain used in this was an indigenous proteolytic Aspergillus, isolated from koji, the intermediate product of soy sauce fermentation. Preliminary test indicated that the crude extracellular enzymes produced by the mold able to inactivate or detoxify AFB1. Gel filtration of the enzyme extract resulted in five protein fractions and al of them able to decrease and detoxify AFB1. The highest specific activity was 3.79 µg AFB1/mg enzyme protein/20 hours. The detoxification products have no observed toxicity effects. It was supposed that the structure of AFB1 was changed and part of AFB1 bound with protein of enzymes.